High perioperative lactate levels as a potential predictor for severe acute kidney injury following aortic arch surgery - Dongxu Wang; Chen Yang; Han Wang; Mengmeng Ye; Chao Xue; Weiguang Wang; Bo Yu; Kai Ren; Zhenxiao Jin; Shiqiang Yu; Shiqiang Yu; Weixun Duan (Frontiers in Medicine)
BackgroundAcute type A aortic dissection (ATAAD) is a life-threatening condition that often requires total aortic arch replacement (TAR) combined with frozen elephant trunk (FET) implantation. Despite advancements in surgical techniques and preoperative management, postoperative acute kidney injury (AKI) remains a prevalent complication that significantly affects patient prognosis, particularly severe AKI. The aim of this study was to investigate the predictive value of perioperative lactate levels in severe postoperative AKI after TAR.MethodsA cohort analysis of 328 patients who underwent TAR with frozen elephant trunk implantation at Xijing Hospital, Xi’an, China, between September 2019 and September 2023 was conducted. Patients were categorized according to AKI severity into non-AKI, mild-AKI, and severe-AKI cohorts, and lactate levels were measured at nine perioperative time points. The primary endpoint was severe AKI (Kidney Disease: Improving Global Outcomes stage 3). Uni-and multivariate logistic regression analyses were performed to identify risk factors for severe AKI. Subgroup analysis substantiated the robustness of lactate levels in predicting severe AKI.ResultsIn total, 45.4% of patients developed mild AKI postoperatively and 20.7% developed severe AKI. Patients with severe postoperative AKI exhibited higher preoperative lactate levels. Multivariate stepwise backward logistic regression analysis identified lactate levels at 12 h postoperatively ([Lacpo12h], cutoff value: 3.3 mmol/L; sensitivity: 63.2%; specificity: 72.3%) as an independent predictor of severe AKI. The subgroup analysis underscored the consistent predictive capacity of Lacpo12h. The 30-day mortality rate was markedly elevated in the severe-AKI cohort, with deceased patients exhibiting a significantly higher Lacpo12h.ConclusionAmong patients with acute type A aortic dissection undergoing TAR, high perioperative lactate levels were closely associated with postoperative AKI. Lacpo12h is a reliable and effective predictor of severe postoperative AKI, highlighting its clinical utility in risk stratification and management strategies.